Planned Peri-Extubation Fasting in Critically Ill Children: An International Survey of Practice - Nabialek, Tomasz; Tume, Lyvonne N.; Cercueil, Eloise; Morice, Claire; Bouvet, Lionel; Baudin, Florent; Valla, Frederic V. (Frontiers in Pediatrics, 2022)
Introduction: Cumulative energy/protein deficit is associated with impaired outcomes in pediatric intensive care Units (PICU). Enteral nutrition is the preferred mode, but its delivery may be compromised by periods of feeding interruptions around procedures, with peri-extubation fasting the most common procedure. Currently, there is no evidence to guide the duration of the peri-extubation fasting in PICU. Therefore, we aimed to explore current PICU fasting practices around the time of extubation and the rationales supporting them. Material and methods: A cross sectional electronic survey was disseminated via the European Paediatric Intensive Care Society (ESPNIC) membership. Experienced senior nurses, dieticians or doctors were invited to complete the survey on behalf of their unit, and to describe their practice on PICU fasting prior to and after extubation. Results: We received responses from 122 PICUs internationally, mostly from Europe. The survey confirmed that fasting practices are often extrapolated from guidelines for fasting prior to elective anesthesia. However, there were striking differences in the duration of fasting times, with some units not fasting at all (in patients considered to be low risk), while others withheld feeding for all patients. Fasting following extubation also showed large variations in practice, with some units withholding nutrition for many hours, and others starting oral feeding based on child demand. The risk of vomiting/aspiration and reducing nutritional deficit were the main reasons for fasting children or reducing fasting times respectively. Discussion: This variability in practices suggests that shorter fasting times might be safe. Shortening the duration of unnecessary fasting, as well as accelerating the extubation process could potentially be achieved by using other methods of assessing gastric emptiness, such as gastric point of care ultrasonography (POCUS). Yet only half of the units were aware of this technique, and very few used it.